1993
DOI: 10.1002/anie.199308801
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Valence Tautomerism of Cobalt Complexes Containing the Benzosemiquinone Anion as Ligand

Abstract: The transformation from CoII to CoIII (e.g., 1 → 2) is displayed by the compounds of type 1 in solution when the temperature is lowered (L is a bidentate N‐donor ligand with a diimine structure, 3,5‐dtbsq− the 3,5‐di‐tert‐butylbenzosemiquinone anion, and 3,5‐dtbcat− the corresponding catecholate ion). In the process one electron is transferred from the Co center to one of the 3,5‐dtbsq− ligands to form the catecholate ligand. Microcrystalline samples in which L is phenanthroline undergo the transformation abru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(69 citation statements)
references
References 19 publications
4
65
0
Order By: Relevance
“…For instance, whereas in complex [Co(bpy)(3,6-DBSQ)(3,6-DBCat)] bipyridine ligands of adjacent molecules stack to form a onedimensional lattice resulting in a remarkable photomechanical effect upon irradiation, replacement by the 3,5-di-tert-butylcatecholato induces a dimerization. As far as the ancillary ligand is concerned, Hendrickson et al [39] and Pierpont et al [40] have also concluded that it is possible to systematically control valence tautomerism by changing the counterligand chelate ring flexibility and their donor abilities. Another interesting example has been described by Awaga et al, who reported valence tautomerism in the spinlabeled complex [Co(nnbpy)(3,5-DTBSQ) 2 ] (4), where nnbpy is a bipyridine substituted nitronyl nitroxide radical.…”
Section: Cobalt Complexesmentioning
confidence: 99%
“…For instance, whereas in complex [Co(bpy)(3,6-DBSQ)(3,6-DBCat)] bipyridine ligands of adjacent molecules stack to form a onedimensional lattice resulting in a remarkable photomechanical effect upon irradiation, replacement by the 3,5-di-tert-butylcatecholato induces a dimerization. As far as the ancillary ligand is concerned, Hendrickson et al [39] and Pierpont et al [40] have also concluded that it is possible to systematically control valence tautomerism by changing the counterligand chelate ring flexibility and their donor abilities. Another interesting example has been described by Awaga et al, who reported valence tautomerism in the spinlabeled complex [Co(nnbpy)(3,5-DTBSQ) 2 ] (4), where nnbpy is a bipyridine substituted nitronyl nitroxide radical.…”
Section: Cobalt Complexesmentioning
confidence: 99%
“…Here, the close proximity of energies between frontier orbitals for the metal centers and radical ligands not only leads to strong coupling, but can also induce electron transfer between the metal and the ligand in these complexes. This electron-transfer process is known as valence tautomerism, and is currently an active area of research in the field of molecular magnetism [52,[134][135][136][137][138].…”
Section: Benzosemiquinonoid Radical-containing Complexesmentioning
confidence: 99%
“…[2,3] Photoinduced spin-state interconversion in spin-crossover iron(ii) complexes has been described. [4] Transient interconversions were also observed at room temperature for valence tautomeric complexes, [5] but recently it was found that a low-spin cobalt(iii) complex of the general formula [ls-Co III (NÀN)(cat)(sq)] (NÀN is a diimine ligand, cat and sq represent the catecholato and semiquinonato forms of 3,5-di-tert-butylcatechol) undergoes transition to the high-spin isomer [hs-Co II (N À N)(sq) 2 ] after illumination at low temperature. [6,7] We have recently observed that the same phenomenon occurs for the 1:1 cobalt-macrocycle dioxolene adduct [Co III (cth)(phencat)](PF 6 )·H 2 O (cth = (dl)-5,7,7,12,14,14-hexamethyl-1,4,8,11-tetraazacyclotetradecane, phencat = catecholato form of 9,10-phenanthrenequinone).…”
mentioning
confidence: 92%